Development of an electrocoagulation equipment for wall paint wastewater treatment - Forero-Buitrago, Gonzalo Alberto; Hernández Lara, Rocío; Rojas, Omar (Universidad del Valle, 2020)
This article describes the tests carried out to evaluate the process efficiency water treatment by electrocoagulation in construction paint wastewater. Electrocoagulation process consists of an electrolytic reactor, equipped with a current source and electrodes responsible for providing the destabilizing ions of colloidal particles, so that they replace the function of the chemical compounds used in conventional wastewater treatment. For the experimental design, we use drinking water and wall paint, in order to treat the solution by electrocoagulation in a treatment scale plant to compare the results before and after treatment, the variables to be measured are: dissolved oxygen (DO); turbidity; pH; conductivity; temperature; chemical oxygen demand (COD).After review the efficiencies obtained, we proceed to the development of an equipment treatment that can treat the wastewater from washing brushes and rollers to be reused again in the washing, avoiding contamination caused by washing tools after painting surfaces in construction processes.

En este artículo se describen las pruebas realizadas para evaluar la eficacia del proceso de tratamiento de aguas por electrocoagulación en aguas residuales de pinturas de construcción. El proceso de electrocoagulación consiste en un reactor electrolítico, dotado de una fuente de corriente y electrodos encargados de aportar los iones desestabilizadores de las partículas coloidales, de forma que sustituyen la función de los compuestos químicos utilizados en el tratamiento convencional de las aguas residuales. Para el diseño experimental, utilizamos agua potable y pintura mural, con el fin de tratar la solución por electrocoagulación en una planta de tratamiento a escala para comparar los resultados antes y después del tratamiento, las variables a medir son: oxígeno disuelto (OD); turbidez; pH; conductividad; temperatura; demanda química de oxígeno (DQO).Después de revisar las eficiencias obtenidas, se procede al desarrollo de un equipo de tratamiento que pueda tratar las aguas residuales procedentes del lavado de brochas y rodillos para ser reutilizadas de nuevo en el lavado, evitando la contaminación provocada por el lavado de las herramientas después de pintar las superficies en los procesos de construcción.
Desarrollo de un equipo de tratamiento de agua residual de pintura de construcción mediante electrocoagulación
Keywords: Electrólisis; Electrólisis del agua; Aguas residuales - Purificación; Electrocoagulation; Electrolysis; Industrial Wastewater Treatment; Electrocoagulación; Electrolisis; Tratamiento de agua industrial.